2012
DOI: 10.1097/dbp.0b013e31825b8482
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Emerging Mental Health Concerns in Youth Perinatally Infected With HIV and Peer Comparisons

Abstract: Objective Cross-sectional research indicates high rates of mental health concerns among youth with perinatal HIV infection (PHIV), but few studies have examined emerging psychiatric symptoms over time. Methods Youth with PHIV and peer comparisons who were HIV-exposed but uninfected or living in house-holds with HIV-infected family members (HIV-affected) and primary caregivers participated in a prospective, multisite, longitudinal cohort study. Groups were compared for differences in the incidence of emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
85
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 68 publications
(84 reference statements)
13
85
2
Order By: Relevance
“…attention deficit hyperactivity disorder), and emotional disorders (e.g. anxiety and depressive disorders) [3][4][5][6][7][8] Psychiatric disorders among children and adolescents with HIV leads to psychological distress and impaired quality of life, increased stigma and isolation and may lead to negative clinical and behavioral outcomes. Despite antiretroviral therapy improving the survival of HIV-infected children, the mental health problems of these children and adolescents have had less attention [9].…”
Section: Introductionmentioning
confidence: 99%
“…attention deficit hyperactivity disorder), and emotional disorders (e.g. anxiety and depressive disorders) [3][4][5][6][7][8] Psychiatric disorders among children and adolescents with HIV leads to psychological distress and impaired quality of life, increased stigma and isolation and may lead to negative clinical and behavioral outcomes. Despite antiretroviral therapy improving the survival of HIV-infected children, the mental health problems of these children and adolescents have had less attention [9].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a call for better psychosocial care of HIV-positive patients (Eaton, McCay, Semrau, Chatterjee, Baingana, Araya, … Saxena, 2011) to address their unique psychosocial issues (Gadow, Angelidou, Chernoff, Williams, Heston, Hodge, & Nachman, 2012;Steele, Nelson, & Cole, 2007). Gadow et al (2012) reported higher than expected rates of psychological problems in HIV-infected children.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the performance of the PHIV youths was poorer compared to the control group, which consisted of agematched HIV-uninfected volunteers [44] . In regard to mental health, the incidence of psychiatric disorders is higher among PHIV adolescents and uninfected youths belonging to HIV-infected families compared to the general population [45][46][47] . Several studies found that up to 70% of such adolescents meet psychiatric diagnostic criteria.…”
Section: Metabolic Complicationsmentioning
confidence: 99%
“…Several studies found that up to 70% of such adolescents meet psychiatric diagnostic criteria. Some authors found correlations between diagnosis in adolescents and psychiatric disorders among their caretakers [45][46][47] .…”
Section: Metabolic Complicationsmentioning
confidence: 99%